Improved Root Growth by Liming Aluminum-Sensitive Rice Cultivar or Cultivating an Aluminum-Tolerant One Does Not Enhance Fertilizer Nitrogen Recovery Efficiency in an Acid Paddy Soil - Hao Qing Zhang; Xue Qiang Zhao; Yi Ling Chen; Jia Lin Wang; Ren Fang Shen (Plants, 2020)
The root is the main site of nitrogen (N) acquisition and aluminum (Al) toxicity. The objective of this study is to investigate whether liming and cultivation of an Al-tolerant rice (Oryza sativa L.) cultivar can improve root growth, thereby increasing N acquisition by rice plants in acid paddy soil. Two rice cultivars (‘B690’, Al-sensitive, and ‘Yugeng5’, Al-tolerant) were cultivated with 15N-labeled urea, and with or without lime in an acid paddy soil (pH 4.9) in pots. We examined root and shoot growth, soil pH, soil exchangeable Al, N uptake, 15N distribution in plant-soil system, and fertilizer N recovery efficiency. Results showed that liming improved the root growth of ‘B690’ by decreasing soil exchangeable Al concentrations, in both N-limited and N-fertilized soils. Liming enhanced the N uptake of ‘B690’ only in the absence of N fertilizer. The root weight of ‘Yugeng5’ was greater than that of ‘B690’ without lime, but the two cultivars showed similar N uptake. The fertilizer N recovery efficiency and N loss did not differ significantly between limed and non-limed conditions, or between the two rice cultivars. Thus, liming an Al-sensitive rice cultivar and cultivating an Al-tolerant one improves root growth, but does not enhance fertilizer N recovery efficiency in the present acid paddy soil.